Qualidade de vida no trabalho (QVT): estudo em um campus fora de sede de uma universidade federal - Arantes, Maria Do Carmo (2018)
The theme Quality of Working Life (QWL) is present on the speeches of leaders and managers of public and private organizations, on the media and on scientific literature of work and health’s science. The growth of the interest in the thematic followed the changes that the working’s scenario has been going through for decades. This study intends to contribute for the discussion of QWL by bethinking the occidental ideas about work, reporting the treatment given to QWL since the decade of 1950, describing the main models for QWL analysis found in the area’s literature, discussing aspects related to its conceptualization and analyzing the topic’s treatment in the public sector, especially in the Varginha/MG campus of the Federal University of Alfenas (UNIFAL-MG), defined as this research’s locus. The overall objective is to diagnose the QWL of this Campus’ workers, in order to include the institution’s QWL Program evaluation. The diagnosis is based on the evaluation model proposed by Hackman and Oldham (1975). As for the objectives, nature, proceedings and the problem’s approach, this research is classified as exploratory and descriptive, applied, field documentary and predominantly quantitative, respectively. The teaching staff, the education administrative technical staff and the outsourced employees compose this research’s population. From the 134 workers on the mentioned Campus, 109 constitute the sample, classified conveniently as non-probabilistic. The instruments used to collect data were institutional documents available on the University’s website, UNIFAL-MG’s Quality of Working Life Committee and questionnaire. The data was obtained by consulting the institutional documents and applying the questionnaire: online for the staff and printed for the outsourced employees. The data were converted to numeric values used as entry on the Statistical Package for Social Sciences’ worksheet in order to analyze frequency, mean value, standard deviation and comparison between the means by the t test. The evaluation of this work’s essential dimensions indicated that the dimensions in need of most changes in the Varginha’s UNIFAL-MG Campus in order to determinate critical psychological states capable of bringing more satisfying personal work results for the teaching and education administrative staff are the extrinsic and intrinsic feedbacks, the ability variety and the autonomy. The seventeen variables that evaluated the perception of the teaching staff’s quality of life obtained satisfactory results in twelve, average in four and unsatisfactory in one. The education administrative staff evaluated seven variables as satisfactory, seven as average and three as unsatisfactory. The research’s participants understand QWL mainly as: an appropriate physical work environment, a payment that allows a good quality of life, learning opportunities and mastering the necessary knowledge and abilities for the position held. The evaluation of the UNIFAL-MG’s staff Quality of Working Life indicated that it needs improvement.